#2**+2 **

\(-\frac{5}{6}=-0.8\overline3\)

\(\frac{2}{3}-\frac{3}{2}\)

Above, there is the original expession. To evaluate this, we must have common denominators. To do this, we must multiply the numerator and the denominator. If you multiply 3 by 2 and 2 by 3, then you will have a common denominator:

\(\frac{2}{3}*\frac{2}{2}=\frac{4}{6}\)

\(\frac{3}{2}*\frac{3}{3}=\frac{9}{6}\)

Notice how I am not actually changing the value of the fraction. I'm multiplying both fractions by 1, so I am not changing the value of the fraction, just the way the number is represented:

\(\frac{4}{6}-\frac{9}{6}=-\frac{5}{6}=-0.8\overline3\)

TheXSquaredFactor
May 23, 2017

#2**+2 **

Best Answer

\(-\frac{5}{6}=-0.8\overline3\)

\(\frac{2}{3}-\frac{3}{2}\)

Above, there is the original expession. To evaluate this, we must have common denominators. To do this, we must multiply the numerator and the denominator. If you multiply 3 by 2 and 2 by 3, then you will have a common denominator:

\(\frac{2}{3}*\frac{2}{2}=\frac{4}{6}\)

\(\frac{3}{2}*\frac{3}{3}=\frac{9}{6}\)

Notice how I am not actually changing the value of the fraction. I'm multiplying both fractions by 1, so I am not changing the value of the fraction, just the way the number is represented:

\(\frac{4}{6}-\frac{9}{6}=-\frac{5}{6}=-0.8\overline3\)

TheXSquaredFactor
May 23, 2017